Programa “Huellas Verdes” para Fortalecer la Conciencia Ambiental - Velásquez Espilco, María Soledad (2026)
This study presents the effect of a quasi-experimental program called Green Footprints on the environmental awareness of fifth-grade students at a school in Chosica. This research, conducted in 2019, applied the program to the experimental group to verify its effects on environmental awareness and its cognitive, affective, dispositional, and active dimensions. The theoretical basis of the research is reflected in the program because it systematically plans actions to solveenvironmental problems and promotes environmental awareness by strengthening knowledge, dispositions, and personal and group actions related to the defense and protection of nature. The active and reflective strategies significantly strengthened the students' environmental awarenessbecause they were committed to solving environmental problems sustainably.